Sympathy towards people infected with COVID-19 mediates relations between media use and death anxiety - Chao, Miao; Liu, Jie; Xue, Dini; Zhang, Bin; Hall, Brian J. (Frontiers in Psychiatry, 2025)
The COVID-19 pandemic threatened mental health. This study examined the longitudinal associations among pandemic-related media use, sympathy for people infected with COVID-19 (PIWC), and death anxiety. 132 Chinese adults completed measures three times, one week apart during the initial phase of COVID. The results showed that media use, sympathy, and death anxiety decreased significantly over the first month of the outbreak. Pandemic-related media use predicted increased future sympathy for PIWC, and sympathy predicted increased future death anxiety. The study identified the short-term effects of media use on sympathy and death anxiety, and suggests that reduced media exposure may be beneficial.